Ibu dan Keterlambatan Bicara pada Anak - Cice Tresnasari; Sigit Gunarto; Lia Marlia Kurniawati; Budiman (UNISBA Press, 2024)
Abstract. Speaking is one aspect of children development. By speaking, children communicate verbally. A child who has delayed speech delay is at risk of experiencing social, emotional, behavioral and cognitive problems. Immediate treatment is needed for child who is suspected of having symptoms of delayed speech so that they develop optimally. Early detection of symptoms of delayed speech is the first step for a child to receive treatment. It is hoped that a mother's good knowledge of speech development can detect symptoms of a child's speech delay. This study aims to determine the relationship between the mother's level of education and age with the mother's level of knowledge about speech development. A total of 32 mothers who had children aged... years as subjects received training on children's speech development as an intervention. To determine changes in knowledge levels before and after training, the Wilcoxon test was used and to analyze the correlation between education level and age with changes in knowledge levels, the Fischer Exact Test was used. The results showed that there was an increase in knowledge before and after the intervention, there was a relationship between education level and knowledge level, but there was no relationship between age and knowledge level. Abstrak. Bicara merupakan salah satu aspek perkembangan anak. Dengan bicara anak berkomunikasi secara lisan. Seorang anak yang terlambat bicara berisiko mengalami masalah sosial, emosi, tingkah laku dan kognitif. Penanganan segera diperlukan anak yang dicurigai memiliki gejala terlambat bicara agar berkembang optimal. Deteksi dini gejala terlambat bicara merupakan langkah awal seorang anak mendapat penanganan. Pengetahuan yang baik dari seorang ibu tentang perkembangan bicara diharapkan dapat mendeteksi gejala terlambat bicara anak. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pendidikan dan usia ibu dengan tingkat pengetahuan ibu tentang perkembangan bicara. Sebanyak 32 orang ibu yang memiliki anak dengan rentang usia… tahun sebagai responden menerima pelatihan tentang perkembangan bicara anak sebagai intervensi. Untuk mengetahui perubahan tingkat pengetahuan sebelum dan sesudah pelatihan digunakan uji Wilcoxon dan untuk menganalisis korelasi tingkat pendidikan dan usia dengan perubahan tingkat pengetahuan digunakan uji Fischer Exact Test. Diperoleh hasil bahwa terjadi peningkatan pengetahuan sebelum dan setelah intervensi, terdapat hubungan antara tingkat pendidikan dan tingkat pengetahuan, namun tidak terdapat hubungan antara usia dan tingkat pengetahuan.